Ovalbumin-specific regulatory T cells differentiated from the naïve phenotype (CD44loCD62Lhi) in mesenteric lymph nodes stably suppress enteropathy even in severe food-allergic mice - Kyoko Shibahara; Tomohiro Hoshino; Haruka Nakanishi; Kosuke Nishitsuji; Kohei Soga; Yoshiyo Bamba; Satoshi Hachimura; Haruyo Nakajima-Adachi (PLoS ONE, 2025)
Impaired expansion, stability, and function of regulatory T cells (Tregs) are reported in patients with severe allergy. Transfer of Tregs is a potential means of treating severe food allergy; however, methods to obtain allergen-specific Tregs with stable regulatory activities are needed. To achieve our goal, we examined the characteristics of allergen-specific Tregs by comparing two mouse strains transgenic for the ovalbumin (OVA)-specific T cell receptor gene: Rag23−3 and RagD10 mice (OVA23−3 and DO11.10 crossed with Rag2 knockout mice, respectively). RagD10 is a tolerant model, whereas Rag23−3 shows severe allergy when fed egg white (EW). To examine the differentiation of CD4+ T cells into Foxp3+ Tregs (induced Tregs; iTregs), CD4+ T cells or whole cells from mesenteric lymph nodes or spleens were cultured under Treg-polarization conditions and stimulated with either a combination of anti-CD3 and anti-CD28 antibodies or OVA plus antigen-presenting cells. After stimulation with the antibodies, iTregs were induced at comparable levels from CD4+ T cells from untreated Rag23−3 and RagD10 mice. Transfer of the resultant iTregs from untreated Rag23−3 mice suppressed allergic responses in EW-fed Rag23−3 mice. In contrast, stimulation with OVA plus antigen-presenting cells prevented the differentiation of iTregs from CD4+ T cells from untreated Rag23−3 mice, suggesting that OVA-induced T-cell receptor signaling inhibits effective Treg differentiation. Furthermore, antibody-mediated differentiation afforded significantly more iTregs differentiation of naïve (CD44loCD62Lhi) CD4+ T cells than of effector/effector memory (CD44hiCD62Llo) T cells isolated from the mesenteric lymph nodes of EW-fed Rag-23–3 mice. Excessive production of interleukin-4 and interferon-gamma by CD4+ T cells from EW-fed Rag23−3 mice significantly inhibited Treg induction in RagD10 mice, suggesting the severe allergic cytokine milieu likely prevents their differentiation. However, our study showed that allergen-specific Tregs with regulatory activity can be obtained from naïve CD4+ T cells from the intestinal immune system of mice even with severe allergy.